The Quiet Sacrifice: How Sexual Coercion Experiences Shape Women's Sexual Wellbeing - Garrido Macías, Marta; Gómez-Pulido, Edgardo Alfonso; Sáez, Gemma; Expósito, Francisca (Anales de Psicología / Annals of Psychology, 2026)
Sexual coercion profoundly impacts women's sexual and relational well-being, necessitating an understanding of its underlying processes. This study examines the relationship between sexual coercion victimization and women's sexual and relationship satisfaction. A cross-sectional design with 113 women in heterosexual relationships assessed experiences of sexual coercion, self-silencing, unmitigated sexual communion, controlled reasons for sex, sexual satisfaction, relationship satisfaction, and sexual desire. Findings indicate that sexual coercion victimization leads to higher levels of self-silencing and prioritization of partners' needs, resulting in lower sexual and relationship satisfaction and reduced sexual desire. The study highlights the need to address self-silencing and prioritization of partners' needs in interventions for sexual coercion victims, offering insights for gender-sensitive programs to mitigate these negative outcomes and encourage full sexual consent.